Homing defects of B cells in HIV-1 infected children impair vaccination responses. Issue 17 (17th April 2019) - Bekele, Yonas; Lemma, Mahlet; Bobosha, Kidist; Yibeltal, Desalegn; Nasi, Aikaterini; Gebre, Meseret; Nilsson, Anna; Aseffa, Abraham; Howe, Rawleigh; Chiodi, Francesca
Highlights: We studied B cell subsets in HIV-1 infected children and their homing properties. B cell phenotypic and homing characteristics were related to HBV vaccine responses. Severe phenotypic dysfunctions identified in B cell subsets in spite prolonged ART. CXCR4 expression was significantly reduced in B cell subsets from HIV+ children. Correlations found between HBV vaccine responses and memory B cells in HIV+ children. Poor response to vaccines in HIV+ children may reside in impaired B cell homing. Abstract: Background: Successful vaccinations rely on antibody responses. Chemokine receptors play an important role in B cell homing to differentiation niches. We assessed CXCR4, CXCR5 and CCR6 expression on B cells during HIV-1 infection and relate it to antibody responses against a HBV vaccine. Methods: Blood was obtained from 54 healthy controls and 38 ART-treated HIV-1 infected children, aviremic (n = 25) or viremic (n = 13). Frequency of naïve and memory B cell subsets was studied by immunostaining. Homing capacity of blood B cells to lymphoid and inflamed tissues was evaluated through CXCR4, CXCR5 and CCR6 expression. Plasma CXCL12 and CXCL13 levels and antibody titers to HBV antigen were determined by ELISA. Results: The frequency of naïve and resting memory (RM) B cells in ART treated children was comparable to control subjects. Profound defects in the homing phenotypes of naïve and memory B cells were identified, with lower CXCR4 and CXCR5 expression. Increased CXCL13 levels were observed in infected children, inversely correlating to CXCR5 expressing B cell subpopulations. Antibody titers to HBV vaccine correlated with frequency of resting and switched memory B cells in HIV-1 infected children. Conclusions: Homing defects of B cells to germinal center may underlie impaired vaccine responses during HIV-1 infection.